Jesus and the Ordained Ministry: A Christocentric View of Priesthood - O'Collins, Gerald (Irish theological quarterly, 2011)
In presenting the priesthood of the ordained, this article emphasizes how it is based on the prior priesthood of all the baptized and forms a ‘vulnerable vocation’ within a ‘vulnerable vocation.’ Expounding Christ’s triple role as priest, prophet, and king/shepherd and the priesthood he exercised during his public ministry, the article recalls how the ordained are visible signs of the invisible, but dynamically present, Christ the High Priest and share as ‘holy intercessors’ in the intercessory role of his eternal priesthood.